2018
DOI: 10.1080/21691401.2018.1479711
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1297 contributes to the progression of human cervical carcinoma through PTEN

Abstract: Our data indicate that miR-1297 contribute to the human cervical carcinoma through PTEN. miR-1297 could be a reasonable miRNA for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Moreover, Ma et al revealed that miR-1275 could pronouncedly abolish the inhibitory effects on cell proliferation and invasion triggered by circMAN2B2 knockdown in A549 and H1299 lung cancer cells [12]. Besides, the results showed that cell proliferation was enhanced while cell apoptosis was declined by miR-1297 overexpression in human cervical carcinoma [28]. As for colony formation, Wang et al revealed that miR-1297 reduced colony formation capacity of glioma cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ma et al revealed that miR-1275 could pronouncedly abolish the inhibitory effects on cell proliferation and invasion triggered by circMAN2B2 knockdown in A549 and H1299 lung cancer cells [12]. Besides, the results showed that cell proliferation was enhanced while cell apoptosis was declined by miR-1297 overexpression in human cervical carcinoma [28]. As for colony formation, Wang et al revealed that miR-1297 reduced colony formation capacity of glioma cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…14 Interestingly, many studies also found that miR-1297 plays a tumor promoting factor in many cancers such as liver cancer, 30 human breast cancer, 31 non-small cell lung cancer 32 and human cervical cancer. 33,34 Wang et al explained that miR-1297 is a tumor-inhibiting factor in glioma. 35 In this report, we also disclosed that loss of miR-1297 recuperates the SNHG5 knockdown-mediated inhibitory effect on cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is one of the most common cancers and the second leading cause of cancer-related death in women worldwide [1,2], with 274,000 deaths annually [3], which is also a complex disease involving the abnormal expression of many oncogenes and tumour suppressor genes [4]. The discovery of novel therapeutics requires a comprehensive understanding of the disease biology.…”
Section: Introductionmentioning
confidence: 99%